The value of the Aesthetic Component of the Index of Orthodontic Treatment Need (IOTN) in the Assessment of Subjective Orthodontic Treatment Need - Haider Zahid, Aiman Niaz, Sofia Shehzad, Sunniya Saeed, Kainat Khan, Palwasha Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Malocclusion is the most common dental problem. Its correction needs assessment before planning Orthodontic treatment. The index of orthodontic treatment need (IOTN) is one of the most valuable method of grading and evaluating malocclusion. A number of studies stated; using the IOTN have reported that there is limited use of aesthetic component in school going children. Objectives: To estimate whether dental concern expressed by the grade of the AC chosen by subjects is reliable and whether it may be predictive for potential co-operation. Materials and Methods: This study was carried out in school going children of 12 year of age in kpk Pakistan. This study was based on a questionnaire and clinical examination. The questionnaire consists of various items. On the basis of these item questionnaire was filled. Clinical examination was done at the schools each time by the same orthodontist. Statistical analysis was done. Results: Out of total children, 29 were female and 58 were male. Most of the children were satisfied with dental aesthetics. Most of them wanted to change colour of the teeth. Most of the enrolled students were classified in “no treatment need’ category” followed by “need borderline treatment” category. Satisfaction with aesthetic were also evaluated (P-value <0.090). Conclusion: It was concluded that large number of people were in need of the orthodontic therapy as per the aesthetic component of IOTN.